Konsep Diri Remaja Jawa saat Bersama Teman - - Sartana; Avin Fadilla Helmi (Faculty of Psychology, Universitas Gadjah Mada, 2014)
The aim of the study was to formulate a theory about Javanese adolescent self-concept in relation with friends. The subjects of this research were three Javanese adolescents, two girls and one boy. Data were collected through in-depth interviews and observation and were analyzed with the so-called grounded theory approach. The results of this study indicated that Javanese adolescents interprets himself as plural selves, hierarchical interdependent and altered. Individuals have a lot of selves that represent their relationships with others. The selves are composed with each other in a hierarchical relationship. In a particular time, an individual activates one only of their selves. The self-activation process goes with the principle of